ANALYSIS OF THE STRUCTURAL CHARACTERISTICS OF TEXTILE-POLYMER COMPOSITIONS USED IN THE FORMATION OF HEADWEARS. - U.R. Saydaliyeva (Modern World Education: New Age Problems – New solutions, 2026)
This article presents the results and analyses of research on the structural characteristics of textile-polymer composites used in shaping headwear.